Analisis struktur ekonomi Provinsi Jambi dan Kabupaten/Kota di Provinsi Jambi tahun 2000-2022 - Putri Sitohang, Yunita; Syaparuddin, Syaparuddin; Emilia, Emilia (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This research aim to analyze: 1) sectoral economic potential in Jambi Province and Regencies/Cities in Jambi Province in 2000-2022; 2) economic structure of Jambi Province and Districts/Cities in Jambi Province in 2000-2022 and shifts in economic structure. The analysis methods used are Location Quentient (LQ), Growth Ratio Model (MRP), Overlay and Shift Share. The results of this research show that there are seven regions that are included in the primary potential sector; Jambi Province, Sarolangun, Batang Hari, Muaro Jambi, Tanjung Jabung Timur and Tebo and Muaro Jambi in the primary sector and secondary. The results of the shift share analysis for Gross Regional Domestic Product (GRDP) contribution show that a shift in economic structure has occurred from the primary sector to the tertiary sector in Kerinci and East Tanjung Jabung. And there has been a shift in the economic structure from the primary sector to the secondary sector in Sarolangun, Batang Hari, Muaro Jambi, Tebo and Bungo. For Jambi Province, Merangin, West Tanjung Jabung and Jambi City there has been no shift in the economic structure.